Research status of magnesium alloys by micro-arc oxidation: a review - Dou, Jinhe; Chen, Yang; Yu, Huijun; Chen, Chuanzhong (Surface engineering, 2017)
Magnesium and its alloys are fascinating candidates for biodegradable implants due to their suitable mechanical properties, biodegradability and biocompatibility. However, the rapid corrosion rate, generation of a large amount of hydrogen gas and increase in local pH of the body fluid limit their potential biomedical applications. Various techniques, including alloying, mechanical processing and surface treatment, have been used to reduce the corrosion rate of materials. Surface treatment is one of the widely used techniques to improve the corrosion resistance of the Mg alloys. Compared to other surface modification processes, micro-arc oxidation can provide good adherent, hard, scratch-resistant, wear-resistant, and corrosion-resistant coatings on magnesium alloys. This article mainly reviews the influence of key relatively process parameters, such as electrolytic composition and presence of additives. Normally, electrolytic system and additives can improve the corrosion behaviour of magnesium alloys using appropriate concentration. The future prospects are summarised as well.